2020
DOI: 10.1136/bmjopen-2019-032884
|View full text |Cite
|
Sign up to set email alerts
|

Developing a framework to incorporate real-world evidence in cancer drug funding decisions: the Canadian Real-world Evidence for Value of Cancer Drugs (CanREValue) collaboration

Abstract: BackgroundOncology therapy is becoming increasingly more expensive and challenging the affordability and sustainability of drug programmes around the world. When new drugs are evaluated, health technology assessment organisations rely on clinical trials to inform funding decisions. However, clinical trials are not able to assess overall survival and generalises evidence in a real-world setting. As a result, policy makers have little information on whether drug funding decisions based on clinical trials ultimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 22 publications
0
55
0
2
Order By: Relevance
“…Harnessing the potential of RWE will require close cooperation between key [13]. Similarly, in Europe, efforts to optimize treatment benefits and leverage RWE for personalized medicine are supported by public/private projects.…”
Section: Future Advancesmentioning
confidence: 99%
“…Harnessing the potential of RWE will require close cooperation between key [13]. Similarly, in Europe, efforts to optimize treatment benefits and leverage RWE for personalized medicine are supported by public/private projects.…”
Section: Future Advancesmentioning
confidence: 99%
“…Multiple jurisdictions are exploring the role of RWE to examine the external validity of clinical trial evidence and enable life-cycle assessment of pharmaceuticals (i.e., assessment at different points of marker approval) [ 12 ]. In Canada, the Canadian Real-world Evidence for Value of Cancer Drugs (CanREValue) Collaboration is one such initiative developing a general framework for the generation and use of RWE to enable life-cycle reassessment to inform ongoing oncology drug funding decisions [ 13 ]. In precision medicine, RWE methods to concentrate clinical trial data with systems-generated RWE are being examined by the Canadian Network for Learning Healthcare Systems and Cost-Effective ‘Omics Innovation (CLEO).…”
Section: The Potential Of Real-world Evidence (Rwe)mentioning
confidence: 99%
“…For example, changing the current Adoption Feasibility criteria of the framework to Implementation and Sustainability which could consider factors such as "drug utilization, budget impact analysis, and an assessment of if and how the funding algorithm has changed since the initial review" was suggested as a modification to the deliberative framework that would allow for its use for questions of reassessment. 81 Furthermore, the collaborative proposed 3 separate recommendation categories in response to a reassessment review: status quo, revisit funding criteria or pricing, do not continue funding, and/or delist.…”
Section: Life-cycle Approach To Htamentioning
confidence: 99%